Comparison of wall construction between interlocking brick system and conventional system / Badrulmunir Berhan - Berhan, Badrulmunir (Universiti Teknologi Mara, Perak, 2018)
ZMA Bina Sdn. Bhd was established in year 2011 with the cooperation between three owners, Encik Zulhamzi Mokhtar, Encik Khairun Anwar and Encik Mazrulnizam. Before the establishment of the company, all of three owners has their own company with different specialty between the each other. Encik Zulhamzi Mokhtar were specialist in building architecture, Encik Khairun Anuar were specialist in building construction and while Encik Mazrulnizam were specialist in building engineering. All of this varieties of specialty between their own made them realize a great opportunity lies in their future if they cooperate together in one company. Their mission for cooperated in one company are to simplify all the affairs of building to the clients. ZMA Bina provides service to client from A to Z started from agreement of the building to the building plan and until the building construction, all in one company. ZMA Bina also provides a lots of house site location to be sold to the clients.